Konsep Emotional Spiritual Quotient (ESQ) dalam Pendidikan Remaja Perspektif Ary Ginanjar Agustian dan Muhammad Utsman Najati - Zahra, Viyona Nur; Nuhdi, Asep; Makmun, Syukron (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This research aims to examine the concept of Emotional Spiritual Quotient (ESQ) in adolescent education based on the perspectives of Ary Ginanjar Agustian and Muhammad Utsman Najati. This research is motivated by the reality of a character crisis experienced by many adolescents today, marked by weak self-control, a loss of life direction, and the degradation of spiritual values. The research was conducted using a library research method with a descriptive and comparative approach. The findings indicate that Ary Ginanjar Agustian, through the ESQ approach, emphasizes the importance of integrating intellectual, emotional, and spiritual intelligence grounded in the Pillars of Faith (Rukun Iman), the Pillars of Islam (Rukun Islam), and the concept of Ihsan. Meanwhile, Muhammad Utsman Najati focuses the ESQ concept on emotional regulation and soul purification based on the Qur'an, Hadith, and Islamic psychology. The ESQ concept proves to be highly relevant in addressing contemporary challenges in adolescent education by instilling divine values, empathy, responsibility, and self-control. Therefore, implementing the ESQ concept within families, schools, and society is essential to shape adolescents who are faithful, virtuous, and resilient.